Optimization of the extrusion process for development of high fibre soybean-rice ready-to-eat snacks using carrot pomace and cauliflower trimmings. (December 2016) - Alam, Mohammed Shafiq; Pathania, Shivani; Sharma, Anjali
Abstract: Ready-to-eat low-cost and nutritious extruded snack was developed from composite flour comprising rice, defatted soybean flour, carrot pomace powder and cauliflower trimmings powder. Experimental design was carried out using Box Behnken design of response surface methodology. Experimental variables included die temperature (125–175 °C), screw speed (300–500 rpm) and cauliflower trimmings and carrot pomace powder (7.5–17.5 g/100 g), pulse powder (7.5–17.5 g/100 g) in rice flour (65–85 g/100 g). Extrudate properties were assessed by analyzing bulk density, expansion ratio, water absorption index, water solubility index, hardness, color change, overall acceptability, protein content and fibre content. Analysis of variance revealed that die temperature had the most significant impact among all variables followed by rice flour. The optimum extrusion conditions were 164 °C die temperature, 313 rpm screw speed and 85 g/100 g rice flour with a desirability value of 76.0%. Results showed that optimum composite flour blends 15 percent of defatted soybean flour, carrot pomace powder and cauliflower trimmings powder in rice flour. The blend proportions under optimum extrusion conditions had improved nutritional quality with 10.25 g/100 g protein and 0.84 g/100 g of fibre content. Highlights: Low cost high protein and high fibre ready-to-eat snack was developed. Snack was produced from rice, defatted soybean, carrot pomace powder and cauliflower trimmings powder. Proximate and functional properties of composite flour were assessed using standard procedures. The optimum flour blends were extruded. Extrusion process conditions were optimized using response surface methodology.